Перспективные направления музейной педагогики в ДОО (из практики организации развивающей предметно-пространственной среды) - Ahtyrskaya Y. V., Tkachenko S. A. (Инновационные технологии в науке и образовании, 2016)
this article discusses the question of organizing a mini-Museum in the kindergarten group, as one of the promising directions in the developmental organization of subject-spatial environment, aimed at implementing educational areas in accordance with GEF TO.
Keywords: предметно-пространственная среда; мини-музей; формирование предметно-пространственной среды; subject-spatial environment; a mini-Museum; the formation of the subject-spatial environment